NEW PRINCIPLES AND EFFECTIVE WAYS OF ALLOYS MODIFYING - V. Yu. Stetsenko (Литьë и металлургия, 2012)
New principles and efficient methods for modification of alloys were developed. They enabled to invent new technological processes for casting of billets with finelydispersed inverted microstructure.